Towards Achieving SDG 7 in Indonesia: Analysis of the Impact of Co? Emissions, Energy Use, and Economic Growth on Renewable Energy Consumption - Zahra, Maharani Altaf El; Prasetyo , P Eko (Journal Research of Social Science, Economics, and Management, 2026)
Indonesia's economic growth has remained relatively stable; however, the accompanying energy consumption patterns have not progressed in tandem with this growth, revealing a misalignment with sustainable development principles. This study explores the influence of economic growth, total energy consumption, and CO? emissions on renewable energy consumption (REC) in Indonesia to provide insights for achieving Sustainable Development Goal (SDG) 7. Utilizing Indonesia's annual data from 2004 to 2021, the analysis employs the Autoregressive Distributed Lag and Error Correction Model (ARDL–ECM). The cointegration test confirms a stable long-term relationship among the variables. In the long run, both total energy consumption and CO? emissions exert a significant negative effect on REC, indicating that increases in these factors are associated with a lower share of renewables, likely due to persistent fossil fuel dependence. Conversely, economic growth exhibits a significant positive influence, serving as a potential driver for renewable energy adoption through enhanced investment capacity. Short-term estimates reveal a strong and rapid adjustment process toward long-term equilibrium, as evidenced by a highly significant Error Correction Term. These findings underscore the critical role of strategically steering the energy transition in Indonesia, highlighting that sustainable economic growth must be deliberately coupled with policies that actively decouple energy demand and emissions from fossil fuels to accelerate renewable energy consumption and achieve SDG 7 targets.